Synoptic weather patterns and their impacts on regional particle pollution in the city cluster of the Sichuan Basin, China. (1st July 2019) - Zhan, Chen-chao; Xie, Min; Fang, De-xian; Wang, Ti-jian; Wu, Zheng; Lu, Hua; Li, Meng-meng; Chen, Pu-long; Zhuang, Bing-liang; Li, Shu; Zhang, Zhi-qi; Gao, Da; et al.
Abstract: Particle pollution is a severe air quality problem, which is usually related to weather patterns. In this study, the relations between regional particle pollution and synoptic weather patterns in the city cluster of the Sichuan Basin (SCB), China are investigated. The data analyses of air quality monitoring records show that particle pollution is extremely serious in the SCB, with the main air pollutants dominated by PM2.5 . According to the geographical locations and particle pollution levels, the 22 typical SCB cities can be classified into three categories. The intercity correlations are very high, implying that there exists regional particle pollution in the SCB. Based on the NCEP (National Center for Environmental Prediction) reanalysis data, synoptic weather classification is conducted with the sum-of-squares technique, and five typical weather patterns are primarily identified. For the weather pattern 4 and 5, there are few days with regional particle pollution. They are considered as the clean weather patterns, and record as P4 and P5 respectively. For other three weather patterns (1, 2 and 3), both the polluted and the clean days are considerable. Their clean (record as P1_C, P2_C and P3_C, respectively) and the polluted (record as P1_P, P2_P and P3_P, respectively) cases are further separated to discuss the exact impact mechanism of weather patterns on regional particle pollution. In the end, three polluted and five clean weather patterns are identified. By synthetically analysing the meteorological factors, the three-dimensional atmospheric circulation structures and the backward trajectories, the influence mechanisms of these eight weather patterns on regional particle pollution are discussed. The results show that the polluted weather patterns are generally associated with higher air pressure, higher relative humidity, lower air temperature and lower wind speed. Particles in the SCB can be locally produced under all weather patterns. For the polluted weather patterns (P1_P, P2_P and P3_P), there is often long-range transportation bringing polluted air masses to the SCB, and local adverse atmospheric circulation tends to obstruct the transport and the diffusion of particles. For the clean weather patterns, the southwest flows from the ocean at the 850 hPa layer are the main cause for the scavenging of particles in P1_C and P3_C, the mitigating impacts of P2_C and P5 are related to rainfalls in autumn and summer, and the alleviating impact of P4 is linked to strong winds from winter monsoon. These findings are consultative for the investigations on the formation mechanism of smog pollution in the SCB. Highlights: Weather patterns' impact on regional particle pollution in SCB is investigated. Three polluted and five clean weather patterns are identified. Particle pollution can be locally formed under adverse weather conditions. Long-range transportation contributes to aggravate particle pollution. Marine air masses, rainfalls and strong winds can alleviate the pollution.